Accessibility of alcohol as a risk factor contributing towards alcohol abuse amongst the youth of a selected rural community in Limpopo Province, South Africa - Rabotata, Enoch; Makhubele, Jabulani; Mafa, Prudence (Technium Social Sciences Journal, 2021)
Alcohol abuse amongst the youth is one of the major problems the world is facing, especially in rural communities where the majority of young people are unemployed and have little to do with their time. This study sought to determine the accessibility of alcohol amongst the youth of a rural community in Limpopo province, South Africa. This was a qualitative study which employed the exploratory case study research design which allowed the researchers to explore the risk factors for youth alcohol abuse. Interviews were conducted to collect data which was analysed thematically. The Eco-systems theory was used as a guiding theory for this study. The study found that there were clear associations between physical availability of alcohol, its affordability and high density of liquor outlets in one area and youth alcohol abuse. This study concluded that alcohol and other substance abuse call for preventative and intervention measures in rural communities targeted at the youth. Issues such as educating parents and guardians on how to improve their parenting skills in relation to alcohol consumption and the dangers thereof proved to be of greater need in the rural communities.